The Role of Parents in Forming Children's Character in Sruwen Village and Duren Village - Solihin, Solihin; Guterres, Juvinal Ximenes (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
The objectives of this research are 1) To analyze how parents' roles are used in shaping children's character in Duren Village and Sruwen Village; 2) To find out how parents' roles differ in shaping children's character in Duren Village and Sruwen Village; 3) To find out how the role of parents is constructed for children in Duren Village and Sruwen Village and its relevance in facing today's millennial generation. The results of the research are: 1) The role of parents in Duren Village is an authoritative parenting style, namely parents who apply a democratic parenting style have clear rules and expectations, and the role of parents in Sruwen Village is an authoritarian parenting style where parents are the responsible party. . center, namely the center of everything. the words/words and wishes of parents are used as benchmarks that must be obeyed by children; 2) The role of parents in Duren Village in shaping children's character through behavior that is very effective in directing children, while the role of parents in Sruwen Village in caring for their children is more concerned with the wishes of parents, children are supervised quite closely, parents always maintain their distance from each other. their children rather than considering their children's wishes; 3) The construction of a democratic parental role in Duren Village will give birth to an assertive personality which is the ideal type so that there are not many weak people. Meanwhile, the construction of the role of authoritarian and permissive parents in Sruwen Village can make children feel unloved, alienated, even hated by their parents, will become individuals who are not independent, easily offended, have a negative view of other people, feel inferior and lack self-confidence. and feel free to act.